Well-Being Inequality and Reference Groups - An Agenda for New Research - Bernard M.S. van Praag (Tinbergen Institute, 2010)
In this paper it is argued that subjective well-being of the individual depends on two types of variables. The first type consists of characteristics of the individual himself, such as age, health, income, etc. The second type of variables consists of the characteristics of the individuals belonging to his reference group. The vast literature about happiness, quality of life, and well-being informs us extensively about the effects of objective variables. How the second type affects well-being is much less investigated. It is argued that the concept of well-being inequality cannot be properly defined without taking the referencing process into account. The reference effect depends on how frequently individuals compare with others and on the degree of social transparency in society. We attempt to give a structural embedding of the idea of reference groups in SWB-models. In this paper we employ the reference-extended model for incorporating in happiness studies the concept of inequality in happiness or SWB. Finally, we plead for an extension of the present happiness paradigm by setting up a new additional agenda for empirical research in order to get quantified knowledge about the referencing process. As a first step we suggest a new question module to be included in new survey questionnaires.
Keywords: D31; D62; D63; I31; 330; subjective well-being; happiness; inequality; reference group; Lebensqualität; Soziale Ungleichheit; Interpersoneller Nutzenvergleich; Externer Effekt; Statistische Methode; Theorie; Deutschland